Microscopic polyangiitis presenting with persistent cough and hemoptysis in pediatrics: A case report and review of the literature - Zhu, Yantong; Zheng, Xiangrong (Frontiers in Oncology, 2022)
Background：Microscopic polyangiitis (MPA) is a necrotizing vasculitis which involves small- and medium-sized vessels, and is associated with the presence of antineutrophil cytoplasmic antibodies with a perinuclear staining pattern (p-ANCA). The kidney and lung are the organs primarily affected. MPA is rare in children, and is easily misdiagnosed. Below is a complete case history of the course of the disease. Case presentation: An 11-year-old girl with one-month history of cough and hemoptysis who had showed no improvement after imipenem-cilastatin treatment. p-ANCA and microscopic haematuria and proteinuria was positive, and a chest CT revealed an area of shadow in bilateral lower lobe of the lungs. Renal biopsies showed crescentic glomerulonephritis, and MPA was diagnosed based on these criteria. The patient exhibited dramatic clinical and imaging improvements after immunosuppressive treatment. Conclusion: The organs most commonly involved in MPA in children are the lungs, kidneys, skin, nervous system organs, and organs of the gastrointestinal tract. Careful examination should be carried out in these patients, while biopsies of the kidney or any other of the organs, remains the gold standard for diagnostic purposes. Pulmonary involvement may be the initial symptom of the disease, and should not be confused with pneumonia. Urinalysis should be performed in patients with hemoptysis. Antibiotics should be used with caution